Um novo modelo de sobrevivência Bell-Inversa Gaussiana com fração de cura - Carregari, Renata Cristina (Universidade Federal de São Carlos, 2021)
In this work we propose a new survival model called the Bell-Inverse Gaussian cure rate. We consider different activation schemes in which the number of factors $M$ has the Bell distribution and the time of occurrence of an event follows the Inverse Gaussian model. The parameters are estimated by the classical and Bayesian methods. In a simulation study, we investigate the mean estimates, biases, mean squared errors and coverage probabilities in different activation schemes. In order to detect possible influential or extreme observations that can cause distortions on the results of the analysis we use the Bayesian method of influence analysis of case deletion based on $\psi$-divergence. Finally, we show the applicability of the proposed model to a real dataset.
A new Bell Inverse Gaussian cure rate survival model
Keywords: Análise de sobrevivência; Distribuição bell; Distribuição Inversa Gaussiana; Esquema de ativação latente; Modelo de sobrevivência com fração de cura; Bell distribution; Cure rate survival model; Inverse Gaussian distribution; Latentactivation schemes; Survival analysis; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA::ANALISE DE DADOS